Maize Plant Resilience to N Stress and Post-silking N Capacity Changes over Time: A Review - Mueller, Sarah M.; Vyn, Tony J. (Frontiers in Plant Science, 2016)
We conducted a synthesis analysis on data from 86 published field experiments conducted from 1903 to 2014 to explore the specific consequences of post-silking N accumulation (PostN) in New Era vs. Old Era hybrids on grain yield (GY) and recovery from plant N stress at flowering (R1 stage). The Old Era encompassed studies using genotypes released before, and including, 1990 and the New Era included all studies using genotypes released from 1991 to 2014. Mean N fertilizer rates for experiments in the Old and New Era were similar (170 and 172 kg ha−1, respectively), but plant densities averaged 5.0 plants m−2 in the Old Era vs. 7.3 plants m−2 in the New Era studies. Whole-plant N stress at R1 for each hybrid, environment and management combination was ranked into one of three categories relative to the N Nutrition Index (NNI). The key findings from this analysis are: (i) New Era genotypes increased the proportion of the total plant N at maturity accumulated post-silking (%PostN) as N stress levels at R1 increased—demonstrating improved adaptability to low N environments, (ii) New Era hybrids maintained similar GY on a per plant basis under both low and high N stress at R1 despite being subject to much higher population stress, (iii) PostN is more strongly correlated to GY (both eras combined) when under severe R1 N stress than under less acute N stress at R1, (iv) the New Era accumulated more total N (an increase of 30 kg N ha−1) and higher %PostN (an increase from 30% in Old to 36% in New Era), and (v) the change in stover dry weight from silking to physiological maturity (ΔStover) has a positive, linear relationship with PostN in the Old Era but less so in the New Era. This increased understanding of how modern genotypes accumulate more N in the reproductive stage and have more PostN and GY resilience to mid-season N stress, even when grown at much higher plant densities, will assist trait selection and N management research directed to improving maize yields and N efficiencies simultaneously.